With the word, health professionals who are at the front line of COVID-19 combat (Research, Society and Development, 2020)
Report the experience of the Life in Quarantine Project with emphasis on the material produced by health professional who are at the front line of Coronavirus (COVID-19) combat. Experience report about the Life in Quarantine Project: mental health in focus. This project aimed to develop actions on social networks in April and May of 2020, by students and professors of two public universities. We highlighted in the article reports of 14 health professionals who are at the front line of COVID-19 combat focusing on their expressions of feelings and behaviors. Health professionals are experiencing challenges already known to their occupation, but now even more maximized. So, they referred to some feelings regarding such experience, like emotional instability; altruism; population appeal; belief in science; faith and hope; and fear of contamination. Pandemics raises the need for better mental health management with factors that enhance the mental well-being of health professionals. Also, there is a need for safety measures sustained by science, so that they operate in order to decrease negative impacts on physical and mental aspects on this public.